Five-year clinical outcomes in patients with significant coronary artery spasm: a propensity score-matched analysis - Byoung, Geol Choi; Park, Sang-Ho; Seung, Woon Rha; Ji, Young Park; Se, Yeon Choi; Yoonjee, Park; Shaopeng , Xu; Ngow, Harris Abdullah; Ali, Jabar; Hu, Li; Ji, Bak Kim; Sunki, Lee; et al. (Elsevier Ireland Ltd, 2015)
Coronary artery spasm (CAS) is known to be a risk factor of acute coronary syndrome and angina pectoris. However, there is no currently available data with larger study population regarding long-term clinical outcomes of CAS in real world clinical practice. We evaluated the prevalence of CAS and the impact of CAS on 5-year clinical outcomes in a series of Asian CAS patients documented by intracoronary acetylcholine (Ach) provocation test. A total of 1413 consecutive patients without significant coronary artery disease (CAD) who underwent Ach provocation test between Nov. 2004 and Oct. 2008 were enrolled. Significant CAS was defined as > 70% of narrowing by incremental intracoronary injection of 20, 50 and 100 μg. Patients were divided into two groups based on the presence of significant CAS (the non-CAS group: n = 640, the CAS group; n = 773). To adjust potential confounders, a propensity score matched (PSM) analysis was performed using the logistic regression model. A total of 54.7% (773/1413) patients were diagnosed as CAS documented by Ach provocation test. After PSM analysis, 2 propensity-matched groups (451 pairs, n = 902, C-statistic = 0.677) were generated. Despite of similar incidence of individual hard endpoints including mortality, myocardial infarction and revascularization, the CAS group showed the higher trend of recurrent angina requiring follow up angiography than the non-CAS group up to 5 years (HR; 1.56, 95% C.I.; 0.99–2.46, p = 0.054). The prevalence of CAS was 54.7%. Although the cumulative incidence of recurrent angina requiring follow up coronary angiography seems to be increased up to 5 years in CAS patients, CAS patients was not associated with major individual and composite clinical outcomes such as mortality, MI, PCI, CVA with optimal medical therapy as compared with patients without CAS.